Subcutaneous Fat Necrosis of Newborn (SCFN) Associated with Head Cooling in an Asphyxiated Newborn-A case report - Rahman, AFMM; Ameri, AA; Shehri, HSA; Mridha, MAA (Bangladesh Journal of Child Health, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bjch.v38i2.21146 Bangladesh J Child Health 2014; VOL 38 (2) : 101-103